Correlation between electrical characteristics and biomarkers in breast cancer cells - Yang Wang (Nature Portfolio, 2021)
Abstract Both electrical properties and biomarkers of biological tissues can be used to distinguish between normal and diseased tissues, and the correlations between them are critical for clinical applications of conductivity (σ) and permittivity (ε); however, these correlations remain unknown. This study aimed to investigate potential correlations between electrical characteristics and biomarkers of breast cancer cells (BCC). Changes in σ and ε of different components in suspensions of normal cells and BCC were analyzed in the range of 200 kHz–5 MHz. Pearson's correlation coefficient heatmap was used to investigate the correlation between σ and ε of the cell suspensions at different stages and biomarkers of cell growth and microenvironment. σ and ε of the cell suspensions closely resembled those of tissues. Further, the correlations between Na+/H+ exchanger 1 and ε and σ of cell suspensions were extremely significant among all biomarkers (pε < 0.001; pσ < 0.001). There were significant positive correlations between cell proliferation biomarkers and ε and σ of cell suspensions (pε/σ < 0.05). The microenvironment may be crucial in the testing of cellular electrical properties. ε and σ are potential parameters to characterize the development of breast cancer.